EFEK PEMBERIAN DIKLAT DAN PENGUATAN KOMPETENSI TERHADAP SIKAP PROFESIONALISME GURU DAN DAMPAKNYA PADA PRESTASI BELAJAR SISWA SD DI LINGKUNGAN UPTD PEUSANGAN KABUPATEN BIREUEN - Win, Ruwaida; Zainuddin (LPPM-UNIKI, 2022)
The purpose of this study was to determine the effect of Training and Teacher Competence on Learning Achievement of Elementary School Students at UPTD Peusangan, Bireuen Regency. The research was conducted on 180 elementary school teachers in the UPTD Peusangan, Bireuen Regency as respondents, the results obtained were: The results of the hypothesis test indicate that there is a positive effect of providing education and training to teachers on the professional attitude of classroom teachers, which is 23.42%. It is proven that the significant influence of the class teacher competence factor on the professional attitude of the teacher is 10.25%. The results of the path analysis between teacher training and student achievement have a significant effect, namely 19.65%. There is a positive influence of teacher competence on student achievement of 24.74%. Simultaneous test results, there is a significant effect of teacher training and teacher competence variables on teacher professional attitudes, which is 33.7%. The results of the regression analysis between the professional attitude of teachers to student achievement, proved significant. Where is 34.20% the influence of teacher's professional attitude in supporting student learning achievement. And the contribution of teacher training and teacher competence factors contributed to increasing student learning achievement reaching 44.3%